Ebbs and Flows : Analyzing Gender and Social Inclusion Issues in India’s Urban Water Supply and Sanitation Sector - World Bank (Washington, DC, 2017)
Cities in the developing world are witnessing unprecedented growth rates. It is expected that 70 percent of the global population will live in cities by 2050. In urban areas, as in rural areas, women and girls are often the primary users, providers, and managers of water in their household, and are the guardians of household hygiene and health. In spaces of urban poverty, such as slums, women and girls experience multiple deprivations that arise from insecurity of land tenure, informal access mechanisms, over- crowding, and the various stresses of urban life. The water supply and sanitation sector, is the juncture at which broader goals of poverty alleviation, social development, gender equality, and sustainable urban development converge. How issues of gender and urban poverty can be addressed comprehensively in the design and implementation of urban water supply and sanitation (UWSS) programs is not yet well understood. In order to address these gaps in knowledge, the World Bank commissioned a study to analyze UWSS issues among the urban poor through a gender and social exclusion lens. Using India, with its burgeoning population and growing number of urban poor, as the context, this study assesses how women, girls, and socially excluded groups are impacted by poor access to water supply and sanitation and how they can be engaged in the design and management of water supply and sanitation programs. It is expected that the findings from this study will inform Government of India’s policies in this sector and assist in the design of future World Bank-supported UWSS projects.